Descripcion de poblaciones silvestres de Lupinus hispanicus Boiá. Et Reuter - Arrieta, V.=700 1 Besga, G.; cordero, S.A.
(Es, En)
ilus., 47 ref.
Keywords: LUPINUS; GERMOPLASMA; RECURSOS GENETICOS; TAXONOMIA; ESPAÑA